Exploring Trends in Transportation Management: A Review of Scientific Papers on Dimension AI Database from 2020-2024 - Timalsina, Prajit Kumar; Parajuli, Suman Kamal (NPRC Journal of Multidisciplinary Research, 2024)
This qualitative study explores contemporary trends and advancements in sustainable transportation management practices, focusing on articles published between 2020 and 2024 and sourced from sustainability journals. A comprehensive search strategy using the Dimension AI database with the keywords "Transportation" and "Management". Articles were first screened by their title, abstract, and keywords, from which 63 manuscripts were chosen for thematic analysis. The key findings were the importance of sustainable traffic management systems, including congestion measures, infrastructure resilience, and environmental impact assessment. Another strand that emerged was data-driven approaches for smart city traffic management, which included novel techniques for effective decision-making. The study has especially highlighted the requirements of strategies that would set up the innovation in modeling techniques and resilience frameworks for transportation management. This study offers significant insight into modern trends in sustainable transportation management, which should be of immense value to policymakers, urban planners, and transportation professionals in seeking ways to overcome the problems associated with modern urban mobility while ensuring environmental sustainability.